Competitividad, corrupción y productividad en la industria de la construcción - Manitio Lopez, Alex Patricio. (2021)
This research aims to determine the correlation between country corruption, infrastructure competitiveness, and productivity as a contribution to the construction industry's GDP. Numerical data were collected using a quantitative approach, compiled, and analyzed, which after being processed were analyzed using Spearman's method to establish the correlation between these variables. Analysis' process was applied to understand which variable best explains the behavior of the data studied. Although there is a correlation between competitiveness and productivity in industry, no correlation has been identified between corruption and the two mentioned variables at the country level. Knowing these correlations can help explain why a country's infrastructure is deficient. This research shows a solid and direct positive correlation between corruption and infrastructure competitiveness. There was no significant correlation between illegality and productivity as a contribution to GDP and infrastructure competitiveness with productivity as a contribution to GDP. In Ecuador, a local application showed similar outcomes, obtaining a robust positive correlation between corruption and infrastructure competitiveness. Through the analysis of principal components, it was observed that the main component PC1 is represented by the corruption and infrastructure competitiveness variables, which have a significant influence on the data studied, highlighting the corruption variable, but in the principal component PC2, it was observed that it is represented by the productivity variable, which indicates that the PC1 component would help us to have a better understanding of the behavior of the data analyzed. The primary component analysis using the PC1 component proposes an equation that helps determine the state of a country related to the construction. When applied, it gets results to fit the reality of the countries under study.